Low-dose developmental exposure to bisphenol A alters the femoral bone geometry in wistar rats. (December 2016) - Lejonklou, M.H.; Christiansen, S.; Örberg, J.; Shen, L.; Larsson, S.; Boberg, J.; Hass, U.; Lind, P.M.
Abstract: Background: Bisphenol A (BPA) is a chemical produced in large volumes for use in manufacturing of consumer products and industrial applications, and an endocrine disruptor known to affect several hormonal systems. Bone produces hormones and is additionally a sensitive hormone target tissue, and is thus potentially sensitive to low doses of endocrine disruptors such as BPA, especially during development. Methods: 110 pregnant Wistar rats were gavaged with 0; 25 μg; 250 μg; 5000 μg or 50, 000 μg BPA/kg bodyweight (bw)/day from gestational day 7 until weaning at postnatal day 22. The three-month-old offspring were sacrificed and right femurs collected for length measurements, geometrical measurements by peripheral quantitative computed tomography (pQCT), as well as for analyses of biomechanical properties using the three-point-bending method. Results: The femur was elongated in female offspring of dams exposed to 25 or 5000 μg BPA/kg bw/day (1.8% and 2.1%, respectively), and increased cortical thickness (4.7%) was observed in male offspring of dams exposed to 25 μg BPA/kg bw/day, compared to controls ( p < 0.005). The biomechanical properties of the bone were not significantly altered. Conclusions: In utero and lactational exposure to the lowest BPA dose used in this study altered femoral geometry in both male and female offspring. This was observed at 25 μg BPA/kg bw/day, a dose lower than the Human Equivalent Dose (HED) applied by EFSA to set a temporary TDI (609 μg BPA/kg bw/day), and far lower than the No-Observed-Adverse-Effect-Level (NOAEL) (5000 μg BPA/kg bw/day) on which the US FDA TDI is based. Highlights: The bone is an endocrine organ and thus potentially sensitive to endocrine disruption. A large number of litters as well as dose groups are included in the study. Low-dose BPA exposure (25 μg/kg bw/day) altered the femoral geometry. The female femur length, and male diaphyseal cortical thickness, was affected. Results of the present study suggest that current risk assessments need re-evaluation.